Academic Integrity in Canada An Enduring and Essential Challenge - Eaton, Sarah Elaine; Christensen Hughes, Julia (Ethics and Integrity in Educational Contexts,, 2022)
This open access book presents original contributions and thought leadership on academic integrity from a variety of Canadian scholars. It showcases how our understanding and support for academic integrity have progressed, while pointing out areas urgently requiring more attention. Firmly grounded in the scholarly literature globally, it engages with the experience of local practicioners. It presents aspects of academic integrity that is specific to Canada, such as the existence of an "honour culture", rather than relying on an "honour code". It also includes Indigenous voices and perspectives that challenge traditional understandings of intellectual property, as well as new understandings that have arisen as a consequence of Covid-19 and the significant shift to online and remote learning. This book will be of interest to senior university and college administrators who are interested in ensuring the integrity of their institutions. It will also be of interest to those implementing university and college policy, as well as those who support students in their scholarly work.